ICT AND INNOVATION ENABLED BUSINESS PERFORMANCE: THE EFFECT OF COVID 19 - Alecia Alecia; Chrisanty Victoria Layman (Universitas Mercu Buana, 2021)
Information communication technology has provided a transformative impetus for how an individual lives, interacts and works. COVID-19 has pushed the cessation of social and economic activities that led Information and Communication Technologies (ICT) as significant tool for business can communicate, store, and manage the necessary information. However not all businesses have the aptitude to change and adopt the necessary ICT to survive such a dynamic market. Therefore, this study aims to examine the influence of ICT, innovation, and corporate entrepreneurship on business performance. This is a quantitative study using a non-probability purposive sampling design. The study includes 204 respondents who are business owners currently using ICT to run their businesses. The data was obtained through online questionnaires and all the data processed and analyzed using SPSS and AMOS. The results show a direct and indirect relationship between ICT and innovation towards business performance, with corporate entrepreneurship as a significant meditating variable. The study brings further empirical proof that ICT literacy needs to paired with innovation and entrepreneurial movement of business that could improve performance.